JISMONIY TAYYORGARLIK JARAYONIDA AKMEOLOGIK YONDASHUVNING DIDAKTIK ASOSLARI - Utepbergenov, A.Q. (SCIENCE and SOCIETY, 2023)
This article briefly describes the didactic basis of the acmeological approach in physical training. The tasks of general physical training, special physical training, theoretical and psychological training are discussed in detail.